A self-routing load balancing algorithm in parallel computing： comparison to the central algorithm - Sadjady, Razieh Sadat; Zamanifar, Kamran (Frontiers of information technology & electronic engineering, 2011)
Load balancing is an important stage of a system using parallel computing where the aim is the balance of workload among all processors of the system. In this paper, we introduce a new load balancing algorithm with new capabilities for parallel systems, among which is the independence of a separate route-finder algorithm between the load receiver and sender nodes. In addition to simulation of the new algorithm, due to similarity in behavior to the proposed algorithm, the central algorithm is simulated. Simulation results show that, the system performance increases with the increase of the degree of neighborhood be- tween the processors. These results also indicate the algorithm＇s high compatibility with environment changes.